The effect of sensitization treatment on chloride induced stress corrosion cracking of 304L stainless steel using U-bend test - Nur Liyana Zakaria, W.W. (Elsevier Ltd, 2019)
Chloride induced stress corrosion cracking (CI-SCC) commonly occurs for 300 series of austenitic stainless steels that are widely used in the petrochemical industry. The occurrence of CI-SCC requires certain circumstances such as corrosive environment, tensile stress, and susceptible material. Heat treatment temperature between 550 °C-650 °C followed by cooling process causes the sensitization of austenitic type stainless steel in which a chromium-depleted band is formed adjacent to the grain boundary. In this study, the impact of sensitization on CI-SCC was examined using austenitic stainless steel grade 304L (SS 304L). The specimens were shaped into U-bend as per ASTM G30 and exposed for long-term immersion test. U-bend samples were heat sensitized at 600 °C for 2 h followed by air cooling. Samples were immersed in 0.1 wt, 1.0 wt and 3.5 wt NaCl into the water bath at temperature of ambient (baseline), 70 °C and 90 °C for 42 days. They were monitored weekly for visual examined for crack. Stereo and optical microscopy were used to identify the CI-SCC and morphology of U-bend specimens. In the beginning, pit corrosion was observed and followed by cracks growth initiated from the localized pit. The results indicated that Cl-SCC was observed for all sensitized SS 304L specimens at elevated temperature conditions which was more susceptible than the as-received type specimens. The trend indicated that the higher the temperature or chloride concentration, the shorter the time for crack initiation. There was no CI-SCC for both types of specimens at ambient condition. Two CI-SCC likelihood graphs with respect to chloride concentration versus temperature are plotted based on the test data. © 2019 Elsevier Ltd. All rights reserved.